Pengaruh Keterlambatan Reward Finansial Terhadap Motivasi Kerja, Loyalitas, dan Retensi Talenta pada Perusahaan Teknologi Informasi: Studi Kasus PT Ihsan Solusi Informatika - Farid Nurdin; Intan Widuri Sakti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of delayed financial rewards on work motivation, employee loyalty, and talent retention in an information technology company. The study was conducted at PT Ihsan Solusi Informatika using a quantitative approach through an employee survey. Data were analyzed using descriptive and inferential statistics to test causal relationships between variables. The results show that delayed financial rewards have a negative and significant effect on work motivation, employee loyalty, and talent retention. These findings emphasize the importance of timely compensation payments as a crucial factor in human resource management in the information technology industry. This study provides practical implications for management in designing fair and sustainable compensation policies.